Pression d’inoculum de la maladie des raies noires (MRN) causée par Mycosphaerella fijiensis Morelet, dans les plantations industrielles de bananiers, en Côte d’ivoire - Essis, B.; Kobenan, K.; Traoré, S.; Yatty, J.; Koné, D.; Aby, N.; Thiémélé, D.E.F. (European Scientific Journal, ESJ, 2016)
The Black Leaf Streak Disease (BLSD) is one of main parasitic constraints of the agro-industrial plantations of banana in the world. Caused by a fungus ascomycete (Mycosphaerella fijiensis Morelet), the losses of yield are up to 50 %, without of resistant cultivars and effective management. This study relative to the level of the disease has been conducted in 12 industrial plantation in 6 production area: Aboisso, Grand- Bassam, Dabou, Agboville, Azaguié and Tiassalé; for a total surface of 2576 ha. The observations concerned the ranks of Youngest Leaf Spotted (YLS), of the Youngest Leaf Necrosed (YLN), the Number of Standing Leaves (NSL) and the gap between the Youngest Leaf Spotted and the Number of Standing Leaves. The results showed that chronic re-infestation of industrial plantation during the last five years, except CDBCI Tiassalé-Songon in 2011 and 2012. An acceptable level of re-infestation was observed in 2012 on other plantations, with the rank of YLS greater than or equal to 3, except BATIA Tiassalé and CDBCI Azaguié. The internal inoculum pressure (YLS) varied a lot from one plantation to another and from one year to another. Except plantation SBMK Aboisso and BATIA Tiassalé, other plantations had at least one value of the rank of the top YLS or equal to 8, during the study indicating a relatively low severity of the BLSD. From 2009 to 2012, all plantations have shown over 8 standing leaves, the minimum required for proper filling of the bunch of banana regime at the time of flowering.